Macrophages in dermal disease progression of phospholipase D4–deficient Fleckvieh calves. Issue 2 (March 2022) - Langenmayer, Martin C.; Jung, Simone; Fux, Robert; Wittlinger, Christina; Tschoner, Theresa; Majzoub-Altweck, Monir; Knubben-Schweizer, Gabriela; Fries, Ruedi; Hermanns, Walter; Trefz, Florian M.
A new gene defect in Fleckvieh calves leads to a syndrome with partial phenotype overlap with bovine hereditary zinc deficiency. A mutation in a gene encoding phospholipase D4 ( PLD4 ), an endosomal exonuclease, causes the disorder. In mice, PLD4 activity indirectly regulates the Toll-like receptor 9 (TLR9) pathway via degradation of microbial DNA. PLD4 absence thus results in visceral macrophage activation comparable to human macrophage activation syndrome. In this study, disease progression and the role of macrophages in affected calves were monitored clinically, clinicopathologically, and histologically over time. Breeding data identified 73 risk matings of heterozygous carriers resulting in 54 potentially PLD4 -deficient calves born on farms. PLD4 status was examined via 5′-exonuclease assay, detecting 6 calves carrying the defect. These were purchased and monitored daily until final necropsy. The calves developed progressive skin lesions starting with small scaling areas terminating in severe crusting dermatitis, especially in areas with mechanical exposure. Histological and immunohistochemical analyses indicated that macrophages with cytoplasmic vacuolation increased considerably in skin sections obtained weekly during the disease course. Macrophage increase correlated with increased dermal lesion severity. Macrophage activation was confirmed by prominent phagocytic activity in the superficial dermis using electron microscopy. Dermal mRNA abundance of CCL2 and CCL3 measured by quantitative polymerase chain reaction verified macrophage activation. Further increase in mRNA of downstream molecule MyD88 and cytokine IL12b connected bovine PLD4 deficiency to increased TLR9 pathway activation. In contrast to human macrophage activation syndrome, the main feature of bovine PLD4 deficiency was local disease in organs with contact to microbial DNA (skin, intestine, lungs).